Cytokine release: A workshop proceedings on the state-of-the-science, current challenges and future directions. (September 2016) - Grimaldi, Christine; Finco, Deborah; Fort, Madeline M.; Gliddon, Daniel; Harper, Kirsty; Helms, Whitney S.; Mitchell, Jane A.; O'Lone, Raegan; Parish, Stanley T.; Piche, Marie-Soleil; Reed, Daniel M.; Reichmann, Gabriele; et al.
Highlights: Proceedings from the ILSI-HESI Workshop on Cytokine Release, October 2013. In vitro human cytokine release assays remain a priority for hazard ID for CRS. Utility of cytokine release assays beyond hazard ID is an area of active research. New assay approaches could lead to better translation of assay results to in vivo. Abstract: In October 2013, the International Life Sciences Institute - Health and Environmental Sciences Institute Immunotoxicology Technical Committee (ILSI-HESI ITC) held a one-day workshop entitled, "Workshop on Cytokine Release: State-of-the-Science, Current Challenges and Future Directions". The workshop brought together scientists from pharmaceutical, academic, health authority, and contract research organizations to discuss novel approaches and current challenges for the use of in vitro cytokine release assays (CRAs) for the identification of cytokine release syndrome (CRS) potential of novel monoclonal antibody (mAb) therapeutics. Topics presented encompassed a regulatory perspective on cytokine release and assessment, case studies regarding the translatability of preclinical cytokine data to the clinic, and the latest state of the science of CRAs, including comparisons between mAb therapeutics within one platform and across several assay platforms, a novel physiological assay platform, and assay optimization approaches such as determination of FcR expression profiles and use of statistical tests. The data and approaches presented confirmed that multiple CRA platforms are in use for identification of CRS potential and that the choice of a particular CRA platform is highly dependent on the availability of resources for individual laboratories (e.g. positive and negative controls, number of human blood donors), the assay through-put required, and the mechanism-of-action of the therapeutic candidate to be tested. Workshop participants agreed that more data on the predictive performance of CRA platforms is needed, and current efforts to compare in vitro assay results with clinical cytokine assessments were discussed. In summary, many laboratories continue to focus research efforts on the improvement of the translatability of current CRA platforms as well explore novel approaches which may lead to more accurate, and potentially patient-specific, CRS prediction in the future.